THE ERGOGENIC POTENTIAL OF RHYTHMIC AUDITORY STIMULATION ON EXERCISE KINETICS AND PSYCHOPHYSIOLOGICAL RESPONSES - Klaudia Brzoza; Filip Matusiak (International Journal of Innovative Technologies in Social Science, 2026)
Background. Music is a recognized ergogenic aid that enhances mood and reduces the Rating of Perceived Exertion (RPE). By modulating the brain's processing of somatic signals, it enables athletes to maintain their effort when they feel this subjectively fatigued.Aim. This review evaluates the impact of music on aerobic and anaerobic performance and RPE, focusing on the roles of synchronization, attentional dissociation, and individual preference.Methods. A comprehensive search of PubMed and Google Scholar databases was conducted for peer-reviewed studies published between 2012 and 2024. The selection included experimental trials and reviews focusing on the psychophysiological and kinetic effects of music in sport and exercise.Results. Music operates through a mechanism of attentional dissociation, reward systems activation and rhythmic entrainment. It increases time to exhaustion during endurance tasks and decreases RPE. For anaerobic effort, it increases the power and alters the technical ability. Personal preference is a significant consideration; Self-Selected Music (SSM) produces greater power, motivation and total work than non-preferred music. Furthermore, music aids metabolic recovery and enhances enjoyment during High-Intensity Interval Training (HIIT).Conclusions. Music optimizes work capacity and exercise tolerance by lowering RPE and stabilizing motor patterns. To maximize its ergogenic potential, practitioners should prioritize athlete-curated, preferred playlists tailored to specific training goals.